2014
DOI: 10.1177/1362361314522353
|View full text |Cite
|
Sign up to set email alerts
|

Fixing the mirrors: A feasibility study of the effects of dance movement therapy on young adults with autism spectrum disorder

Abstract: From the 1970s on, case studies reported the effectiveness of therapeutic mirroring in movement with children with autism spectrum disorder. In this feasibility study, we tested a dance movement therapy intervention based on mirroring in movement in a population of 31 young adults with autism spectrum disorder (mainly high-functioning and Asperger's syndrome) with the aim to increase body awareness, social skills, self-other distinction, empathy, and well-being. We employed a manualized dance movement therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 39 publications
2
107
0
3
Order By: Relevance
“…Alexithymia (4) is common in both somatoform and autistic populations. Somatoform patients benefit from structured authentic movement interventions ( The Body Mind Approach (TBMA) , Payne and Stott, 2010) including a partner exchange, which support the connections between feeling and verbalization; and autists (5) from mirroring in movement—including structured authentic movement—, which can improve their intersubjective abilities (Koch et al, 2014b). This mostly evidence-based literature on the effects of movement therapy on (psycho-)pathological conditions has been summarized in Koch et al (2014a).…”
Section: Embodied Therapiesmentioning
confidence: 99%
“…Alexithymia (4) is common in both somatoform and autistic populations. Somatoform patients benefit from structured authentic movement interventions ( The Body Mind Approach (TBMA) , Payne and Stott, 2010) including a partner exchange, which support the connections between feeling and verbalization; and autists (5) from mirroring in movement—including structured authentic movement—, which can improve their intersubjective abilities (Koch et al, 2014b). This mostly evidence-based literature on the effects of movement therapy on (psycho-)pathological conditions has been summarized in Koch et al (2014a).…”
Section: Embodied Therapiesmentioning
confidence: 99%
“…Adler [33] documented two children’s developmental and interactional improvements during mirroring-based DMT in her classic video documentation “Looking for me” available through the American Dance Therapy Association (). There is one quantitative intervention study demonstrating beneficial effects of DMT on children with autism [34], and one study on adults with ASD [35] namely the feasibility study for this trial. Hartshorne and colleagues [34] showed that 38 children with autism (ages 3–7), after receiving bi-weekly movement therapy in small groups of 3–8 kids led by a trained movement therapist, spent less time wandering, more time showing on-task behavior, less time showing negative responses to being touched, and less time resisting the teacher compared to a matched control group without movement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hartshorne and colleagues [34] showed that 38 children with autism (ages 3–7), after receiving bi-weekly movement therapy in small groups of 3–8 kids led by a trained movement therapist, spent less time wandering, more time showing on-task behavior, less time showing negative responses to being touched, and less time resisting the teacher compared to a matched control group without movement therapy. The feasibility study of our research group [35] showed that after seven sessions of manualized dance movement therapy based on mirroring, young adults with ASD reported improved body awareness, well-being (particularly decreased tension), increased self-other distinction and increased social competence compared to a matched control group of the same rehabilitation institution without the intervention [27]. …”
Section: Introductionmentioning
confidence: 99%
“…Dance/movement therapists apply an empathic reflection of their client's movements (mirroring of the movement quality and/or its form) to build a relationship and enhance emotional understanding between the therapist and the client [35]. A recent 7-week intervention study focusing on mirroring in movement showed improved self-reported social skills in young adults with autism [36], providing some empirical evidence for this notion. …”
Section: Introductionmentioning
confidence: 99%